2003
DOI: 10.1093/annonc/mdg206
|View full text |Cite
|
Sign up to set email alerts
|

Autologous stem cell transplantation for primary refractory Hodgkin’s disease: results and clinical variables affecting outcome

Abstract: In our experience, although overall results of ASCT in PR-HD patients are poor, one-quarter of the patients remain alive at 5 years. Despite this, other therapeutic strategies should be investigated in this group of patients to improve the outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…The outcome of HDC group seems better than that usually reported. The actuarial OS for 70 patients treated with HDC was 43% in the German group, 18 50% at 3 years in a group of 122 HL patients reported by Lazarus et al, 31 about 25% at 5 years in the GEL/TAMO Cooperative Group study 22 and, finally, in the EBMT study dealing with 175 patients with primary induction failure, the actuarial 5-year OS was 36%; however, patients transplanted without further attempts to induce remission with CC had a longer OS comparing with patients who were transplanted after failing to respond to a second-line treatment. 23 Furthermore, Andreè t al.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The outcome of HDC group seems better than that usually reported. The actuarial OS for 70 patients treated with HDC was 43% in the German group, 18 50% at 3 years in a group of 122 HL patients reported by Lazarus et al, 31 about 25% at 5 years in the GEL/TAMO Cooperative Group study 22 and, finally, in the EBMT study dealing with 175 patients with primary induction failure, the actuarial 5-year OS was 36%; however, patients transplanted without further attempts to induce remission with CC had a longer OS comparing with patients who were transplanted after failing to respond to a second-line treatment. 23 Furthermore, Andreè t al.…”
Section: Discussionmentioning
confidence: 83%
“…However, several encouraging reports suggest that HDC can improve outcome in patients with primary refractory HL. [18][19][20][21][22] Current clinical trials in HL are seeking to define the amounts of treatment that produce the optimum therapeutic results. Currently, the three-level scheme of division into early favourable, early unfavourable and advanced disease cases remains a suitable instrument for tailoring riskadapted therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple single-arm studies incorporating both relapsed and refractory HL patients have demonstrated that a salvage approach incorporating HDCT/ ASCT results in durable PFS and OS rates in the range of 40%-50% and 50%-60%, respectively [3,6,[23][24][25][26]. Importantly, patients with refractory disease generally do worse, with durable PFS and OS rates in the range of 15%-32% and 26%-36%, respectively [7,8,23,27,28].…”
Section: Evidence For Hdct/asct and Likelihood Of Successmentioning
confidence: 99%
“…Hodgkin's lymphoma, almost uniquely among human neoplasms, can be cured with the use of HDC/HSCT even when the disease does not respond to standard dose chemotherapy. 45 Although a variety of HDC regimens have been described, no one regimen has been shown to be clearly superior. Currently, popular regimens include CBV (cyclophosphamide, carmustine [BCNU] 17,19,25,50 or high-dose melphalan with or without total body irradiation.…”
Section: Technique Of Hdc/hsctmentioning
confidence: 99%